Extracorporeal shockwave lithotripsy: first 1000 cases at the London Stone Clinic. Issue 6603 (10th October 1987) - Das, G; Dick, J; Bailey, M J; Fletcher, M S; Webb, D R; Kellett, M J; Whitfield, H N; Wickham, J E
Abstract : One thousand patients underwent extracorporeal shockwave lithotripsy for renal and ureteric calculi at this clinic. An overall success rate of 91.8% was achieved (stone free or less than 2 mm fragments at three months) and for stones measuring 1 cm 96.3%. Lithotripsy produced extremely low morbidity, and no deaths have occurred at the clinic. Patients who had lithotripsy alone had a mean hospital stay of three days and in most instances were able to perform their full range of activities on discharge. Planned combination of lithotripsy with minimally invasive endourological procedures such as percutaneous nephrolithotomy and ureterorenoscopy has allowed us to extend the range of treatable cases to include large stones. Prophylactic use of Double-J ureteric stents in selected cases has reduced the incidence of obstruction by stone fragments after lithotripsy, thereby decreasing morbidity and hospital stay.